(untitled) (Medical Forum Monthly, 2024)
Objectives: To compare plating versus Ilizrov external fixation approaches in the management of Schatzker type VI tibial plateau fracture. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Orthopaedics at Liaquat Medical University Hospital Hyderabad/Jamshoro from 25.07.2015 to 24.06.2016. Materials and Methods: All the relevant patients will be admitted to the orthopaedic unit I with schatzker Grade VI tibial plateau fractures, either through casualty or throughout patient department, then divided into two groups (Group 1: Plating management, Group 2: Iliazrov. Schatzker grade I TO V, Open fractures of tibia that requires any kind of flap to cover the naked bone and pathological fracture were excluded from this study. Results: 40 patients of Schatzker type VI fractures were evaluated from which (70%) were male and (30%) were female patients mean age of study subjects was 40.22±11.19 years, with range 18–60 years. Mean age for plating group were 39.22±5.19. 32 (80%) patients had their fracture due to Road Traffic Accident (RTA). The mean time of partial weight bearing (in weeks) was 6.50 ±2.68 weeks (range 6-8 weeks). The mean time of full weight bearing (in weeks) was 15.50±3.20 weeks (range 12-30 weeks). The mean time of union was 10.15 ±2.50 weeks (range 5-20 weeks). The mean time of follow up for the outcome assessment from primary surgery was 25.50±3.50 months (range 17-53 months). The mean hospital stays (in days) was 24.12±4.15 days (range 10 – 30 days). 24 (60%) patients had excellent functional outcome, 10 (25%) patients from plating group and 14 (35%) from Ilizrov group, 12 (30%) patients had good functional and 4 (10%) patients had poor functional results 2 (%) patients from plating group and 2 (5%) patients from Ilizrov group. Over all 13 (32.5%) patients had developed complications, 2 (5%) patients had infected original wound, 4 (10%) patients had pin tract or screw site infection, 9 (22.5%) patients complain pain during walking. Conclusion: Both modalties of treatment have good functional results in different circumstances.